Gender Differences in Mental Health, Institutional Misconduct, and Disciplinary Segregation - Severson, Rachel E. (Criminal justice and behavior, 2019)
Despite a growing body of research on the use of disciplinary segregation within prisons, limited research has examined the role that mental health plays in this context, particularly across gender. This article advances theory and scholarship on disciplinary segregation by examining the role of mental health, violence, and gender. Examining these relationships provides insight into the implications of individual characteristics on in-prison behavior and punishment. Using nationally representative data and logistic regression analyses, this article examines the extent to which mental health history influences disciplinary segregation, if violent misconduct mediates this relationship, and the extent to which gender conditions this relationship. Findings suggest that the measurement of mental health history and violent misconduct are influential in the relationship between mental health history and disciplinary segregation and that gender differences emerge. Implications for theory, research, and policy related to in-prison punishment emerge from the results.